Seeing with new eyes : counseling and the human condition through the lens of Scripture - Powlison, David, 1949-2019. (Phillipsburg, N.J. : P & R Pub., 2003)
This book consists of essays by a highly regarded biblical counselor written over almost twenty years. Some of these pieces exegete Scripture with a counseling perspective, while others recast specific psychological problems. This book explores two main topics. Scripture: Gods voice speaks into real life to reveal the gaze and intentions of the Christ who pursues us. How do we embrace, probe, and unravel Scripture? Understanding people amid their real life struggles: How do we embrace, probe, and unravel the problems of daily life?
Introduction : The gaze of God -- Pt 1. Scripture opens blind eyes. Counsel Ephesians -- Who is God? -- Godly roles and relationships : Ephesians 5:21-6:9 -- Peace, be still : Psalm 131 -- Why me? Comfort from Psalm 10 -- Don't worry : Luke 12:22-34 -- Pt 2. Reinterpreting life. X-ray questions -- I am motivated when I feel desire -- God's love : better than unconditional -- What if your father didn't love you? -- Human defensiveness : the third way -- The ambiguously cured soul -- What do you feel? -- Love speaks many languages fluently -- Biological psychiatry -- Conclusion : Toward simplicity.
Includes bibliographical references (pages 259-267) and index.
Keywords: Pastoral counseling; Bible -- Psychology; Bible; Pastoral counseling; Psychology